Studying the imaginary Samaritan: an investigation of cognitive and social factors affecting patterns of hypothetical helping behavior - Balboa, Nora Jeanette (My University, 2025)
Previous research (Balboa, 2023) has revealed that when directly comparing field data on helping strangers at varying costs to oneself to a hypothetical equivalent, patterns of results differ significantly. This finding contributed to a larger critique of social psychological research methods, which have relied largely on hypothetical surveys in recent history to approximate the choices participants would make in real life social situations (Baumeister et al., 2007). As a result, Study 1 of the current studies sought to expand on this research by investigating how different forms of hypothetical stimuli might influence realistic participant responding in a hypothetical helping paradigm. Study 2, in an effort to more directly manipulate participant responding to avoid the social desirability bias inherent in studies of prosocial behavior, attempted to use metacognitive monitoring strategies to influence honest responding. Finally, Study 3 drew from reciprocal altruism theories to manipulate participants’ valuation of a hypothetical individual in need by lowering or raising the likelihood that they might interact with that person again in the future. Using measures of welfare tradeoff ratio, empathy, and oneness, all three studies additionally investigated the effects of baseline other valuation on the decision to help in a one-shot stranger helping paradigm. Results revealed that though metacognitive and valuation manipulations did not have an effect on helping likelihood across scenarios of different costs to the helper, perceived oneness does seem to influence whether people choose to help strangers. Additionally, patterns of responding across all studies are consistent with those found in the Balboa (2023) field study, especially when stimuli are presented in a first person video format. This finding further supports the role of cost/benefit analysis in the choice to help a stranger and provides a more realistic hypothetical study format for use in helping decision making research
Keywords: Cognition; Altruism; Decision making; Prosocial behavior